Redundancies at North Sydney Ferry Terminal - George, Roy (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1966)
In 1968, following technical change at the North Sydney Ferry Terminal, the working force needed will be 100 men instead of 800 working regularly and 200 on a part time basis. In this article, the author analyses the human problems arising from a technological change and the solutions brought forward by a committee.